2005
DOI: 10.1123/jsep.27.3.350
|View full text |Cite
|
Sign up to set email alerts
|

Some like It Vigorous: Measuring Individual Differences in the Preference for and Tolerance of Exercise Intensity

Abstract: Individuals differ in the intensity of exercise they prefer and the intensity they can tolerate. The purpose of this project was to develop a measure of individual differences in the preference for and tolerance of exercise intensity. The steps involved in (a) item generation and face validation, (b) exploratory factor analysis and item selection, (c) structural validation, (d) examination of the internal consistency and test-retest reliability, (e) concurrent validation, and (f) construct validation are descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
202
3
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 209 publications
(214 citation statements)
references
References 61 publications
8
202
3
1
Order By: Relevance
“…It is proposed that tolerance influences affective responses through cognitive processes in the PFC (Ekkekakis et al, 2005). Consistent with the dual-mode model, sensory input to the body is biologically hard-wired; however, the perception and modulation of the interoceptive input by the PFC may be influenced by predisposed traits.…”
mentioning
confidence: 83%
See 4 more Smart Citations
“…It is proposed that tolerance influences affective responses through cognitive processes in the PFC (Ekkekakis et al, 2005). Consistent with the dual-mode model, sensory input to the body is biologically hard-wired; however, the perception and modulation of the interoceptive input by the PFC may be influenced by predisposed traits.…”
mentioning
confidence: 83%
“…The identification of preference and tolerance as dispositional traits is supported by no change in these scores after a 6-week training program that resulted in improvements in physical fitness (Hall, Petruzzello, Ekkekakis, Miller, & Bixby, 2014). Conceptual validation of the scales (Ekkekakis et al, 2005) showed that neither preference nor tolerance was associated with affective responses reported during exercise at intensities below VT. However, both scales were positively associated with affective responses at VT, but only the tolerance scale related to affective responses above VT (Ekkekakis et al, 2005;Ekkekakis, Lind, Hall, & Petruzzello, 2007).…”
mentioning
confidence: 93%
See 3 more Smart Citations